Implementasi Web Service Integrasi Data Penelitian dan Pengabdian Masyarakat dengan SISTER Ristekdikti dengan Metode REST - Lettisia Apriolita Harjono; Leo Willyanto Santoso; Justinus Andjarwirawan; Resmana Lim (Jurnal Infra, 2020)
Every universities is obliged to apply research and community service. Based on data frm the official website of Ristekdikti, the number of lecturers at universities in Indonesia is very large, so we need a system to collect data and manage lecturer data. With so many data held by the lecturer, the data collection becomes ineffective when having to retype it. Therefore, a program was made to help lecturers to collect research and community service data through data that was already in the university’s information system. This research uses a web service that has been provided by SISTER Ristekdikti. The method used is Representational State Transfer (REST). Data from the university is about research and community service. Input data must be mapped first to fit the required data. The program of this research will provide the success of adding data to SISTER Ristekdikti. The test result of the research program show that the data has been successfully entered into the SISTER Ristekdikti mirror database. From the results of the questionnaire obtained the results that the overall application is good with an average value of 2.7. In addition, the application helps lecturers to complete P2M data and the data displayed in accordance with needs with an average value of 3.